Culture v. Capital: The Rebecca Belmore Case - India Young (Contemporaneity: Historical Presence in Visual Culture, 2014)
This paper considers a civil suit between an artist and her former gallery dealer. In the case of Nadimi v. Belmore, the plaintiff and the defendant exemplify two opposing ideologies, which in turn reflect two possibilities for understanding art. This paper considers the case, and Belmore’s artworks as representative of both systems. Through a strategic defense of her art and her practice, Belmore upholds a complex understanding of the value of art. The current legal system, however, only ascribes art value as commodity product. This paper demonstrates how Belmore’s actions and artworks related to the case supersede simple categorization. Her works cannot be corralled into any one classification; they are not only fine art, nor simply First Nations art. The article exposes how her works deploy multiple socio-cultural systems simultaneously: from an Anishnabe worldview, to European-Canadian art history, from the public museum, to the commercial gallery, to the Toronto bound freeway. I contend that this strategic employment of multiple systems is recognized in newly established international law, and articulated in the United Nations Declaration of Indigenous Peoples as traditional knowledge. The Belmore case illustrates the immediate need for governmental systems to acknowledge and employ such international law to redress systemic misconceptions of Indigenous arts practices.